2012
DOI: 10.4161/onci.19854
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 signaling induces the release of microparticles by tumor cells that regulate inflammatory cytokine IL-6 of macrophages via microRNA let-7b

Abstract: Tumor cells expressing TLRs is generally recognized to mediate tumor inflammation. However, whether and how tumor TLR signaling pathways negatively regulate tumor inflammation remains unclear. In this report, we find that TLR4 signaling of H22 hepatocarcinoma tumor cells is transduced through MyD88 pathway to actin cytoskeletons, leading to the release of microparticles (MPs), the cellular membrane-derived vesicles. As a result, tumor macrophages take up MPs and acquire MP-contained microRNA let-7b, which atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 35 publications
(37 reference statements)
1
38
0
3
Order By: Relevance
“…Previous studies have demonstrated that several molecules or receptors can induce cytoskeletal remodeling. Toll-like receptor 4 induces remodeling via phosphorylation of the myosin light chain for the release of microparticles, thus regulating tumor inflammatory microenvironment (17). Goodwin et al (18) reported that, in motor neuron cells, CDK-5 regulates microtubule orientation and in cancer, Strock et al (8) reported that inhibiting the activity of CDK5 resulted in changes in the microtubule cytoskeleton, loss of cellular polarity and loss of motility in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that several molecules or receptors can induce cytoskeletal remodeling. Toll-like receptor 4 induces remodeling via phosphorylation of the myosin light chain for the release of microparticles, thus regulating tumor inflammatory microenvironment (17). Goodwin et al (18) reported that, in motor neuron cells, CDK-5 regulates microtubule orientation and in cancer, Strock et al (8) reported that inhibiting the activity of CDK5 resulted in changes in the microtubule cytoskeleton, loss of cellular polarity and loss of motility in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…30 Many signals are capable of inducing cytoskeletal alteration, including TLR4 signaling, commonly existed in the tumor microenvironment, that can be transduced to cellular cytoskeletons of tumor cells, leading to their releasing MPs. 31 In addition, hypoxia, nutrient deficiency and apoptotic signals also induce tumor cells to produce MPs in tumor microenvironment. In practice, both chemotherapy and radiotherapy cause abundant tumor cell death, leading to their releasing MPs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a variety of signal molecules in tumor microenvironment can also stimulate tumor cells to produce MPs. 16 In practice, both chemotherapy and radiotherapy can kill plenty of tumor cells, leading to the production of MPs. Therefore, the generation of tumor cellderived MPs (T-MP) might be a very common phenomenon in tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%